The Review of Cybercrime Case Handling Based on Indonesian Jurisdiction and International Law - Aurora Tifani Suci; Fadhila Triza Nandrini; Fazrul Rahman Mukhsin; Achmad Rofiq; M. Ongko Khoirurozy (International Journal of Law and Legal Ethics, 2023)
The purpose of writing this journal is to explain how jurisdictional arrangements in handling cybercrime are governed by national law and international law. The method used in this writing is a library research method using a normative juridical approach and the development of the sources listed in this paper comes from various literature and laws and regulations. The results of the discussion of this journal, international law that regulates state jurisdiction in the Convention on Cybercrime, but the regulation still uses the general concept of jurisdiction in international law. So, it can be concluded from this paper that even though the Cybercrime Convention has not been ratified in Indonesia, the Indonesian people can see from the constitution that we have, namely the ITE Law, that the ITE Law is also a related regulation contained in the Cybercrime Convention. The limitations in this discussion only extend to the discussion regarding jurisdictional arrangements in instruments of international law and national law. Therefore, this article is written to provide understanding to the surrounding community that law enforcement or jurisdiction related to cybercrime has not been implemented either nationally or internationally.